HIGH DOSE VITAMIN C ADMINISTRATION EFFECT IN LEYDIG CELLS, SERTOLI CELLS NUMBER, AND SPERM QUALITY ON MALE WISTAR RATS - Dwi Juniatiningrum, Ratna; Nasihun, Taufiqurrachman; Isradji, Israhnanto (Sains Medika: Jurnal Kedokteran dan Kesehatan, 2018)
Introduction: Most infertile male are associated with poor spermatogenesis due to oxidative stress, and can be prevented with vitamin C. However, excessive amount of high dose of vitamin C can hindered and lower the sperm quality. Objective: To prove that high dose vitamin C is capable to decrease the number of leydig cells, sertoli cells, and sperm quality on male wistar rats.Methods: This research was using experimental method with Post Test Only Controlled Group Design. Of 24 male Wistar rats, divided randomly to 4 groups. Normal groups (Nor -G), only given 2 ml/day distilled water; vitamin C group (VC18-G, VC36-G, and VC72-G) given 18 mg/day, 36 mg/day and 72 mg/day vitamin C respectively, dissolved in 2 ml of distilled water. Sperm, the number of Leydig cells and Sertoli cells were taken from the epididymis and left right testicle on day 21. Sperm analysis using WHO standard, while the number of Leydig cells and Sertoli cells with HE staining.Results: Mann Whitney analysis indicated that the number of sperm in VC36-G and VC72-G are lower compared to that of Nor-G and VC18-G groups, p <0.05. Post-Hoc LSD analysis showed that the lowest number of Leydig and Sertoli Cell, and the weakest sperm motility and morphology  in VC36-G and VC72-G groups, compared to that of Nor-G and VC18-G groups, p <0.05 .Conclusion: Vitamin C 36 and 72 mg/day were capable of reducing Leydig and Sertoli cells number, and worsen sperm quality, characterized by decreased in sperm concentration, motility and morphology in Wistar male- rats.